Hippotherapy in Rehabilitation Care for Children With Neurological Impairments and Developmental Delays: A Case Series. Issue 1 (January 2019) - Kraft, Kathryn A.; Weisberg, Janet; Finch, Michael D.; Nickel, Amanda; Griffin, Kristen H.; Barnes, Timothy L.
Abstract : Purpose: This report assesses functional mobility in children with neurological impairments and documented gross motor delays, before and after receiving either hippotherapy or standard outpatient physical therapy (PT). Summary of Key Points: This is a case-series report using data previously collected for a discontinued randomized controlled trial, in which participants received hippotherapy or standard outpatient clinic PT for a 12-week treatment period. Results demonstrated both subjective and objective functional mobility improvements after treatment in participants receiving hippotherapy and standard outpatient PT, as determined by the Peabody Developmental Motor Scales-2, the Pediatric Evaluation of Disability Inventory, and the Goal Attainment Scaling. Statement of Conclusion and Recommendations for Clinical Practice: When compared with standard outpatient PT, hippotherapy appears to be a viable treatment strategy for children aged 2 to 5 years with neurological impairments and gross motor delays, but additional research in this area is needed to validate findings. Abstract : This case series assesses functional mobility in children with neurological impairments and documented gross motor delays, before and after receiving either hippotherapy or outpatient physical therapy.